2015
DOI: 10.1016/j.physio.2015.03.3465
|View full text |Cite
|
Sign up to set email alerts
|

Associations between cognitive performance and pain in chronic fatigue syndrome: comorbidity with fibromyalgia does matter

Abstract: Background: In addition to the frequently reported pain complaints, performance-based cognitive capabilities in patients with chronic fatigue syndrome (CFS) with and without comorbid fibromyalgia (FM) are significantly worse than those of healthy controls. In various chronic pain populations, cognitive impairments are known to be related to pain severity. However, to the best of our knowledge, the association between cognitive performance and experimental pain measurements has never been examined in CFS patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 44 publications
1
12
0
2
Order By: Relevance
“…and Sarzi‐Puttini et al . The enhanced temporal summation in the CFS/FM group is in accordance with earlier studies …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…and Sarzi‐Puttini et al . The enhanced temporal summation in the CFS/FM group is in accordance with earlier studies …”
Section: Discussionsupporting
confidence: 92%
“…Therefore, central sensitization presumably occurs in a subgroup of RA patients, as assumed in the reviews of Meeus et al 9 and Sarzi-Puttini et al 11 The enhanced temporal summation in the CFS/FM group is in accordance with earlier studies. 15,36 This study did not reveal a significant difference in CPM between groups. However, inferior CPM in CFS/ FM patients had been described in several earlier studies.…”
Section: Baseline Comparisonmentioning
confidence: 57%
“…First, pressure pain thresholds (PPT) and TS were measured by manual algometry on the lower back, quadriceps, trapezius, and hand. TS started 2 minutes Differences in Pain Processing a constant rate (1kg/s) to the tissue surface, bilaterally at 4 spots: erector spinae muscle (lower back) at 5 cm laterally of the processus spinosus vertebrae at L3 (28), quadriceps muscle (quadriceps) at the middle between anterior superior iliac spine and basis patella (26), trapezius muscle (trapezius) at the middle between acromion and processus spinosus at C7 (29)(30)(31), and the web (hand) between the index finger and thumb at the dorsal hand side (13,32). For each site, 2 PPT measurements were taken with a 30 second interval (29) and the mean of both recordings was used for further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Our study follows on from 2 earlier studies which used the same patient groups (29,30). The first of these 2 studies showed that patients with CFS scored higher on symptom severity and worse on handgrip strength, muscle recovery, and cognitive performance compared to patients with MS and controls (29).…”
Section: Discussionmentioning
confidence: 88%